PERSEPSI TOKOH ADAT DAN TENTANG TRADISI UPACARA ADAT KEMATIAN DALAM SISTEM KEKERABATAN DALIHAN NATOLU DI KECAMATAN PAYUNG SEKAKI KELURAHAN LABUH BARU BARAT PEKANBARU - Hotma Hasugian; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the perception of usual leaders. Implementation of the tradition of death ceremonies consisting of 3 levels of usual death of batak, namely matua sari, saur matua and mauli bulung, whether it remains good or there A shift has occurred in traditional ceremonies. Namely the role of Dalihan Natolu in the implementation of adat, the use of meat from slaughtered / farmed animals, used ulos, the fees used in large numbers in traditional ceremonies are reasonable or not. Regarding the research population, 34 figures and those who are aware of adat. by using qualitative approach techniques, (Sugiyono, 2015). Sugiyono, (2015) said that